Full-thickness resection device (FTRD) for treatment of upper gastrointestinal tract lesions: the first international experience - Hajifathalian, Kaveh; Ichkhanian, Yervant; Dawod, Qais; Meining, Alexander; Schmidt, Arthur; Glaser, Nicholas; Vosoughi, Kia; Diehl, David L.; Grimm, Ian S.; James, Theodore; Templeton, Adam W.; Samarasena, Jason B.; Chehade, Nabil El Hage; Lee, John G.; Chang, Kenneth J.; Mizrahi, Meir; Barawi, Mohammed; Irani, Shayan; Friedland, Shai; Korc, Paul; Aadam, Abdul Aziz; Al-Haddad, Mohammad; Kowalski, Thomas E.; Smallfield, George; Ginsberg, Gregory G.; Fukami, Norio; Lajin, Michael; Kumta, Nikhil A.; Tang, Shou-jiang; Naga, Yehia; Amateau, Stuart K.; Kasmin, Franklin; Goetz, Martin; Seewald, Stefan; Kumbhari, Vivek; Ngamruengphong, Saowanee; Mahdev, Srihari; Mukewar, Saurabh; Sampath, Kartik; Carr-Locke, David L.; Khashab, Mouen A.; Sharaiha, Reem Z. (Endoscopy International Open, 2020)
Background and study aims The Full-Thickness Resection Device (FTRD) provides a novel treatment option for lesions not amenable to conventional endoscopic resection techniques. There are limited data on the efficacy and safety of FTRD for resection of upper gastrointestinal tract (GIT) lesions.Patients and methods This was an international multicenter retrospective study, including patients who had an endoscopic resection of an upper GIT lesion using the FTRD between January 2017 and February 2019.Results Fifty-six patients from 13 centers were included. The most common lesions were mesenchymal neoplasms (n = 23, 41 %), adenomas (n = 7, 13 %), and hamartomas (n = 6, 11 %). Eighty-four percent of lesions were located in the stomach, and 14 % in the duodenum. The average size of lesions was 14 mm (range 3 to 33 mm). Deployment of the FTRD was technically successful in 93 % of patients (n = 52) leading to complete and partial resection in 43 (77 %) and 9 (16 %) patients, respectively. Overall, the FTRD led to negative histological margins (R0 resection) in 38 (68 %) of patients. A total of 12 (21 %) mild or moderate adverse events (AEs) were reported. Follow-up endoscopy was performed in 31 patients (55 %), on average 88 days after the procedure (IQR 68–138 days). Of these, 30 patients (97 %) did not have any residual or recurrent lesion on endoscopic examination and biopsy, with residual adenoma in one patient (3 %).Conclusions Our results suggest a high technical success rate and an acceptable histologically complete resection rate, with a low risk of AEs and early recurrence for FTRD resection of upper GIT lesions.